DESIGN AND IMPLEMENTATION OF SOCIAL MEDIA CONTENT MARKETING STRATEGY TO INCREASE PURCHASE INTENTION AND CUSTOMER ENGAGEMENT AT PT SAMHA CATRA NUSANTARA - Amalia, Syifa; Sarah, Ira Siti; Lastari, Hidya Indira (Target : Jurnal Manajemen Bisnis, 2025)
The development of marketing in the digital era requires companies to optimize marketing through social media to reach a wider and more interactive audience. This project aims to design and implement a social media content strategy to increase purchase intent and customer engagement at PT Samha Catra Nusantara, a property company in the East Bandung area. The method used is descriptive with ob- servation techniques, interviews, SWOT analysis, and performance data monitoring through Instagram Insights, TikTok Analytics, and Phlanx. The content strategy developed includes various types of con- tent such as educational, promotional, entertainment, interactive, and testimonials, with the application of elements such as hooks, visual storytelling, music, captions, Call to Action (CTA), and hashtags, as well as content consistency. In addition, the AIDA (Attention, Interest, Desire, Action) approach was applied to strengthen the message structure in each content. The evaluation results showed increased engagement rate and audience response to the designed content. The project also produced a digital content guidebook that can be used by both internal teams and external marketers (Farmer). Practically, the project results provide concrete solutions in digital-based property marketing strategies, strengthen- ing the company’s position amid industry competition.